(1531) The role of female extension workers in developing rural women-A case study of El-Daqahlia governorate دور المرشدات الزراعيات في تنمية المرأة الريفية - دراسة حالة محافظة الدقهلية - Hasanin, Mahasen Mostafa (The Institute of National Planning, 2018)
Assuming that development is the ultimate goal of a continued series of qualitative and quantitative changes that take place in a given society, the aim of development is to rationalize the method which man uses to deal with his environment in order to control it and realize the utmost human welfare for him and the society.